Optical properties of one-dimensional photonic crystal and light absorption enhancement in planar a-Si:H solar cell. Issue 1 (February 2021) - Sadoun, B; Mouetsi, S; Hocini, A; Hocini, A
Abstract: The generation of the photovoltaic has intensified over the last decade, moving from the most basic applications based on elementary devices to one of the most important applications of energy. Photonic Crystals (Ph.Cs) are very promising systems for applications in the field of electromagnetic waves and for real achievements in microwaves field. This particular property of the Ph.Cs offers the possibility of the control of light propagation in an increased way, and thus makes possible to consider many applications in nanotechnology and photovoltaic field. The a:Si-H is a very attractive material for simulation and experimental applications, when deposited in thin layers, it has an efficient refractive index. The Plane Wave Expansion (PWE) method was used to assess the band gap of the structure, the Rigorous Coupled-Wave Analysis (RCWA) method integrated in RSoft CAD Software was used to calculate the optical properties, integrates with thin film structure of the solar cell with Ph.Cs. The one-dimensional optical properties of photonic crystal with the absorbent layer of photovoltaic cell on both hydrogenated amorphous silicon (a:Si-H) and silicon (Si) are studied in this paper in order to enhance the yield of the absorption of light on a solar cell with an efficiency geometrical parameters.